2016
DOI: 10.1097/md.0000000000002572
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Intravesical Chemotherapy and Bacillus Calmette–Guerin Versus Bacillus Calmette–Guerin Monotherapy in Intermediate- and High-risk Nonmuscle Invasive Bladder Cancer

Abstract: Urothelial carcinoma of the bladder has become a major cause of morbidity, mortality, and health-related costs. There is still no standard instillation therapy against bladder cancer. A meta-analysis was conducted to evaluate the efficacy and toxicity of adding chemotherapy to Bacillus Calmette–Guerin (BCG) in intermediate- and high-risk nonmuscle invasive bladder cancer (NMIBC).All randomized controlled trials (RCTs) that evaluated the efficacy of combination therapy and BCG monotherapy for intermediate- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
12
3
Order By: Relevance
“…Intravesical BCG is used to prevent the recurrence and progression of nonmuscle invasive bladder cancer after the TUR procedure. [ 9 ] First described by Morales et al [ 10 ] in 1976, intravesical BCG after TUR is known to provide a significant advantage over TUR alone in delaying tumor recurrence in patients with medium/high-risk Ta or T1 bladder cancer. [ 11 ] The immune response triggered by BCG to the bladder urothelium activates proinflammatory cytokines and promotes neutrophils, monocytes/macrophages, lymphocytes, natural killer cells, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intravesical BCG is used to prevent the recurrence and progression of nonmuscle invasive bladder cancer after the TUR procedure. [ 9 ] First described by Morales et al [ 10 ] in 1976, intravesical BCG after TUR is known to provide a significant advantage over TUR alone in delaying tumor recurrence in patients with medium/high-risk Ta or T1 bladder cancer. [ 11 ] The immune response triggered by BCG to the bladder urothelium activates proinflammatory cytokines and promotes neutrophils, monocytes/macrophages, lymphocytes, natural killer cells, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials and a meta-analysis have produced conflicting results regarding the success of treatments using BCG with intravesical interferon-alpha versus BCG alone [ 10 16 , 39 , 40 ]. Interferon-alpha has been combined with BCG in several studies and the role of this combination continues to be evaluated.…”
Section: Consensus Recomendationsmentioning
confidence: 99%
“…Several reports have found that complete resection of the visible tumor and intravesical instillation of Bacillus Calmette-Guérin (BCG) is the preferred treatment for carcinoma in situ (CIS) in the prostatic urethral mucosa. [1618] Treatment of urothelial carcinoma invading the prostatic ducts is still a controversial issue. Many scholars advocate radical surgery in patients with ductal invasion, [19,20] whereas Palou Redorta et al reported that patients with CIS involving the prostatic ducts could be treated with intravesical BCG, which has a 70% complete response rate.…”
Section: Discussionmentioning
confidence: 99%